2019
DOI: 10.1016/j.jpha.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Development of a microcomposite with single-walled carbon nanotubes and Nd2O3 for determination of paracetamol in pharmaceutical dosage by adsorptive voltammetry

Abstract: This study presents for the first time a new composite of carbon paste (CP), single-walled carbon nanotubes (SWCNTs) and Nd2O3 (NdOX). This versatile composite (NdOX-SWCNT/CPE) was applied to the oxidation of paracetamol (PCM). The newly formed surface was characterized by scanning electron microscopy (SEM), electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). The results showed greater conductivity and a higher surface area for the composite than those of the carbon paste alone. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 43 publications
3
11
1
1
Order By: Relevance
“…The electrode modification procedure was performed as previously reported, with only the incorporated substance changed [23]. Briefly, 50.0 mg of graphite powder and 30 μL of paraffin oil were used for the unmodified electrode.…”
Section: Electrode Preparation (Cu C /Cpe)mentioning
confidence: 99%
“…The electrode modification procedure was performed as previously reported, with only the incorporated substance changed [23]. Briefly, 50.0 mg of graphite powder and 30 μL of paraffin oil were used for the unmodified electrode.…”
Section: Electrode Preparation (Cu C /Cpe)mentioning
confidence: 99%
“…Most studies of the detection of PCM and AR using electroanalytical techniques involve the use of carbon electrodes modified with different types of materials, most commonly carbon nanotubes for PCM [7] and graphene for RA [8]. In the case of PCM, other substances are used with carbon nanotubes to make more sensitive sensors; some of these substances are polymers such as poly (3,4-ethylenedioxythiophene) [9,10] and chitosan [11], and other materials including gold nanoparticles [12], nickel nanoparticles [13], neodymium oxide [14], lanthanum oxide [15] and cationic surfactants [16]. In these studies, PCM oxidation was observed between 0.18 and 0.45 V with a detection limit between 0.0030 and 1.69 μmol/L.…”
Section: Introductionmentioning
confidence: 99%
“…We measured a peak-to-peak separation value of 0.09 V for both electrodes. The deviation of the latter from its theoretical value was due to the conducting nature of the spray-coated SWCNTs [29,30].…”
Section: Resultsmentioning
confidence: 99%